2011
DOI: 10.1128/jcm.02303-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Multiple Single-Nucleotide Polymorphisms in Pneumocystis jirovecii Pneumonia: Development of a Multiplex PCR-Single-Base-Extension Methodology

Abstract: Pneumocystis jirovecii pneumonia (PcP) is a major cause of respiratory illness in patients with AIDS. The identification of multiple single-nucleotide polymorphisms (SNPs) at three distinct P. jirovecii loci encoding dihydrofolate reductase (DHFR), mitochondrial large-subunit rRNA (mtLSU rRNA), and superoxide dismutase (SOD) was achieved using multiplex-PCR (MPCR) followed by direct sequencing and two single-base extension (SBE) techniques. Four SNPs (DHFR312, mt85, SOD215, and SOD110), correlated previously w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 37 publications
2
42
2
1
Order By: Relevance
“…It has been suggested that the epidemiological factors inherent in geographical locations may influence the transmission and circulation of different P. jirovecii genotypes (8,28,37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the epidemiological factors inherent in geographical locations may influence the transmission and circulation of different P. jirovecii genotypes (8,28,37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other sites have failed to find nonsynonomous mutations in DHFR from P. jirovecii, suggesting failure of therapy is not uniquely linked to mutations in DHFR (7)(8)(9)(10). Although DHPS mutations apparently contribute to clinical failure by conferring resistance to sulfamethoxazole (1,2), the appearance of mutations in both DHPS and DHFR in clinical isolates and the apparently more frequent development of DHFR mutations among patients who did receive prophylaxis that included an inhibitor of DHFR suggest a selection pressure is exerted on DHFR by exposure to trimethoprim or pyrimethamine (2).…”
mentioning
confidence: 99%
“…Mutations leading to amino acid substitutions in DHPS have been linked to resistance to sulfamethoxazole (1). Mutations leading to amino acid substitutions in dihydrofolate reductase of Pneumocystis jirovecii have also been observed worldwide for over a decade, but attempts to link clinical outcomes to these mutations have been inconclusive (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…However, some studies on Pneumocystis genetic diversity have reported significant association between some singlenucleotide polymorphisms (SNPs) and clinical parameters in patient with PcP. Notably, SNPs at position 110 and 215 in the sod locus were described and associated with favourable outcome of PcP (SOD215C ) (Esteves et al 2010) or a lower parasite burden (SOD215C/SOD110T) (Esteves et al 2011(Esteves et al , 2012. The mitochondrial MnSOD is probably not the unique component of the Pneumocystis antioxidant system (Fig 6).…”
Section: Discussionmentioning
confidence: 96%